REPRESENTASI PEREMPUAN REMAJA MAKASSAR DALAM CERITA DWIBAHASA KITTAK PAPPASANG MANGE RI BULAN KARYA RAHMAT. R - Rahmi Mardatillah; Nur Hasbi (Panrita: Jurnal Bahasa dan Sastra Daerah serta Pembelajarannya, 2026)
This research aims to describe and analyze the representation of Makassar adolescent girls in the bilingual story Kittak Pappasang Mange Ri Bulan by Rahmat R, particularly in relation to the internalization of the values of pappaissengang, pappasang, and pakainga’. This research employs a qualitative approach with a descriptive-analytical type. The data source is the story text, while the research data consist of excerpts representing values and female identity. Data collection techniques were conducted through reading and note-taking, while data analysis used an interactive model, including data reduction, data display, and conclusion drawing. The results show that the representation of women is constructed through three main dimensions: identity formation, the internalization of affection and education, and the awareness of maintaining self-honor. Women are represented as individuals actively engaged in the process of “becoming” through knowledge, experience, and cultural values. Furthermore, this representation is dynamic and negotiative, combining traditional values with a modern, reflective, and adaptive sense of identity. Thus, this story functions not only as a medium for language learning but also as a means of character education and the preservation of local culture.